ጉብኝት ለመልካም ተሞክሮ - International Livestock Research Institute (International Livestock Research Institute, 2011)
ይህ ዶኪመንቴሽን በግብርናው ዘርፍ የሴቶች መብትና ተሳትፎ እንዲሁም ተጠቃሚነት ተግባራዊ ለማድርግ የ IPMS (በኢትዮጵያ ምርታማነትና የገበያ ስኬት ማሻሻያ) ፕሮጄክትን እንቅስቃሴዎች አካቶ ይዟል። IPMS ሴቶችን ከወንዶች እኩል የፕሮጀክቱ ድገፍ ተጠቃሚ በማድረግ የስርዐተ ፆታ እኩልነትን ለማስፈን የበኩሉን አስተዋፆ አድርጓል። ይህ ዶኪመንቴሽን በአደኣ ወረዳ ያሉ ሴት አርሶ አደሮች በፕሮጀክቱ አማካኝነት በተደረገ የባለሞያ እገዛና የገበያ ትስስር ተጠቃሚ የሆኑበትንና ሰኬታቸውን ይዞ ቀርቧል። This video presents experience of Improving Productivity and Market Success (IPMS) project on its gender mainstreaming strategy to ensure that both men and women farmers benefit from project interventions. This documentary video highlights processes and activities of IPMS to for an active role of women in market oriented agriculture. The case women farmers involved in various crop and livestock production activities in Adaa district, Oromiya, Ethiopia, who benefited from the IPMS project is highlighted on this video. In Amharic with English subtitles.